MENA region as a potential hydrogen supplier for the European market: Analysing a prospective route between Kingdom of Saudi Arabia and Germany - Ali Abdelshafy; Martin Lambert; Grit Walther (The Oxford Institute for Energy Studies, 2024)
Green hydrogen emerges as a promising solution to the intermittency of renewable energy resources, offering storage and transport capabilities essential for a sustainable energy future. However, establishing a viable supply chain poses challenges due to high conversion costs and logistical complexities. Hence, considering the cost dynamics of the entire supply chain is crucial to derive effective strategies and policies. Also, international collaboration is deemed necessary to bridge the gap between regional supply and projected demand. Hence, the paper investigates the green hydrogen's potentials as an energy carrier, addressing the challenges and opportunities in terms of production, trade, and utilization from an interdisciplinary perspective. Herein, the analyses focus on the potential hydrogen route from the Gulf region (the Kingdom of Saudi Arabia) to Europe (Germany) as an illustrative case study. The study emphasizes the importance of factoring in uncertainties, externalities, technological advancements, and transportation while assessing the economic viability of the potential value chain and trading route. Additionally, location strategies, product selection, competitiveness, and geopolitical factors all play significant roles in shaping the green hydrogen market. For potential exporters like Saudi Arabia, addressing these strategic aspects is essential to capitalize on their renewable energy potentials and establish themselves as key players. The discussion also delves into the perspectives of exporters (e.g. KSA) and importers (e.g. Germany), revealing key considerations for each party and suggesting appropriate strategies to mitigate risks and uncertainties.
Keywords: 330; decarbonization; Germany; green hydrogen; hydrogen transport; Saudi Arabia